Berberine HCl and diacerein loaded dual delivery transferosomes: Formulation and optimization using Box-Behnken design - Siddharth Singh; Rajendra Awasthi (International Association of Physical Chemists (IAPC), 2024)
Introduction: Berberine is a poorly water-soluble alkaloid compound showing significant anti-inflammatory characteristics. It reduces the levels of pro-inflammatory and inflammatory cytokines, including tumour necrosis factor (TNF-????, IFN-????) and interleukin (IL-23, IL-12, and IL-23). Diacerein significantly reduces the splenomegaly associated with psoriasis. It downregulates the production of TNF-α and IL-12. Method: This study reported the development of transferosomes containing berberine HCl and diacerein using a film hydration method followed by optimization using a Box-Behnken design. Sodium deoxycholate was used as an edge activator. The impact of independent variables (amount of phosphatidylcholine, amount of edge activator, and sonication cycles) on dependent variables (particle size and entrapment efficiency) was examined. The optimized formulation was characterized for polydispersity index, vesicle size, entrapment efficiency, ζ potential, spectral analysis like Fourier transform infrared, thermal analysis, X-ray diffraction, deformability, transmission electron microscopy, antioxidant assay, in-vitro release, and ex-vivo skin permeation studies. Results: The optimized formulation had a particle size of 110.90±2.8 nm with high entrapment efficiency (89.50±1.5 of berberine HCl and 91.23±1.8 of diacerein). Deformability, polydispersity index, ζ potential, and antioxidant activity of the optimized formulation were 2.44, 0.296, -13.3, and 38.36 %, respectively. Optimized transferosomes exhibited 82.093±0.81 % and 85.02±3.81 % release of berberine HCl and diacerein after 24 h of dissolution study. The transdermal flux of optimized formulation was 0.0224 µg cm-2 h-1 (2.24 cm h-1 permeation coefficient) and 0.0462 µg cm-2 h-1 (4.62 cm h-1 permeation coefficient), respectively, for berberine HCl and diacerein. Raman analysis of treated pig skin confirmed that the transferosomes can permeate the skin. No change in the skin condition or irritation was observed in BALB/c mice. Formulation stored at 4 and 25±2 °C / 60±5 % relative humidity was stable for 3 months. Conclusions: Thus, the results demonstrated successful optimization of the transferosomes for the efficient topical delivery of berberine HCl and diacerein in the effective management of psoriasis.